Community perceptions of mass screening and treatment for malaria in Siaya County, western Kenya. (December 2016) - Shuford, Kathryn; Were, Florence; Awino, Norbert; Samuels, Aaron; Ouma, Peter; Kariuki, Simon; Desai, Meghna; Allen, Denise
Abstract Background Intermittent mass screening and treatment (iMSaT) is currently being evaluated as a possible additional tool for malaria control and prevention in western Kenya. The literature identifying success and/or barriers to drug trial compliance and acceptability on malaria treatment and control interventions is considerable, especially as it relates to specific target groups, such as school-aged children and pregnant women, but there is a lack of such studies for mass screening and treatment and mass drug administration in the general population. Methods A qualitative study was conducted to explore community perceptions of the iMSaT intervention, and specifically of testing and treatment in the absence of symptoms, before and after implementation in order to identify aspects of iMSaT that should be improved in future rounds. Two rounds of qualitative data collection were completed in six randomly selected study communities: a total of 36 focus group discussions (FGDs) with men, women, and opinion leaders, and 12 individual or small group interviews with community health workers. All interviews were conducted in the local dialect Dholuo, digitally recorded, and transcribed into English. English transcripts were imported into the qualitative software programme NVivo8 for content analysis. Results There were mixed opinions of the intervention. In the pre-implementation round, respondents were generally positive and willing to participate in the upcoming study. However, there were concerns about testing in the absence of symptoms including fear of covert HIV testing and issues around blood sampling. There were fewer concerns about treatment, mostly because of the simpler dosing regimen of the study drug (dihydroartemisinin–piperaquine) compared to the current first-line treatment (artemether–lumefantrine). After the first implementation round, there was a clear shift in perceptions with less common concerns overall, although some of the same issues around testing and general misconceptions about research remained. Conclusions Although iMSaT was generally accepted throughout the community, proper sensitization activities—and arguably, a more long-term approach to community engagement—are necessary for dispelling fears, clarifying misconceptions, and educating communities on the consequences of asymptomatic malaria.